2017
DOI: 10.5539/jel.v6n3p265
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for New Teachers and Ways of Coping with Them

Abstract: The first year of a teacher's career can determine their longevity within the field of education. The issues of first year teachers were analyzed through a grounded theory qualitative research analysis. The results of this study indicate that a first year teacher may feel stress, lack appropriate support, and may feel unprepared to handle behavioral and academic issues among their students. Based on the literature review, the implementation of mentoring programs between new and experienced teachers not only be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 8 publications
0
32
0
3
Order By: Relevance
“…These kinds of initiatives could be shared with friends, family members and peers to promote social support, which has been found to be effective promoting well-being. 58 …”
Section: Discussionmentioning
confidence: 99%
“…These kinds of initiatives could be shared with friends, family members and peers to promote social support, which has been found to be effective promoting well-being. 58 …”
Section: Discussionmentioning
confidence: 99%
“…The problems are however slightly different from those who have served for long. Usually the problems that are faced by new teachers such as teaching work overload, lack of support from other teachers, discipline challenges in classroom and classroom managements (Dias-Lacy & Guirguis, 2017). The problems faced by these new teachers are usually due to the lack of preparation either during the course of teaching or before starting the service as a new teacher (Darling-Hammond et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These weaknesses cause students with backgrounds of high-poverty, high minority schools, non-native for English lesson (Alam, 2019) or at any though conditions such mild mentally retarded children (Widodo et. al, 2019) tend to give big challenges to teachers who are underprepared and inexperienced (Dias-Lacy & Guirguis, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that about half of the newly qualified teachers quit teaching during the first five years. The main reasons brought out for deciding to quit include the great workload of teachers and discontent with working conditions (including inadequate resources and support), inadequate preparation for the teacher job, handling the work stress and family-related reasons [4], [6], [7], [8], [9], [10].…”
Section: Theoretical Backgroundmentioning
confidence: 99%